100 pengetahuan tentang Romawi Kuno / Fiona Macdonald ;alih bahasa, Angelina A. Hapsari ; penyunting, Rudiyanto, B. Waluyo - MACDONALD, Fiona; Hapsari, Angelina A; Rudiyanto; Waluyo, B (Pakar Raya, 2006)
48 hlm ilus 29 cm